Tropical savanna small mammals respond to loss of cover following disturbance: A global review of field studies - Bergstrom, Bradley J.; Scruggs, Samuel B.; Vieira, Emerson M. (Frontiers in Ecology and Evolution, 2023)
Small-mammal faunas of tropical savannas consist of endemic assemblages of murid rodents, small marsupials, and insectivores on four continents. Small mammals in tropical savannas are understudied compared to other tropical habitats and other taxonomic groups (e.g., Afrotropical megafauna or Neotropical rainforest mammals). Their importance as prey, ecosystem engineers, disease reservoirs, and declining members of endemic biodiversity in tropical savannas compels us to understand the factors that regulate their abundance and diversity. We reviewed field studies published in the last 35 years that examined, mostly experimentally, the effects of varying three primary endogenous disturbances in tropical savanna ecosystems—fire, large mammalian herbivory (LMH), and drought—on abundance and diversity of non-volant small mammals. These disturbances are most likely to affect habitat structure (cover or concealment), food availability, or both, for ground-dwelling small mammalian herbivores, omnivores, and insectivores. Of 63 studies (included in 55 published papers) meeting these criteria from the Afrotropics, Neotropics, and northern Australia (none was found from southern Asia), 29 studies concluded that small mammals responded (mostly negatively) to a loss of cover (mostly from LMH and fire); four found evidence of increased predation on small mammals in lower-cover treatments (e.g., grazed or burned). Eighteen studies concluded a combination of food- and cover-limitation explained small-mammal responses to endogenous disturbances. Only two studies concluded small-mammal declines in response to habitat-altering disturbance were caused by food limitation and not related to cover reduction. Evidence to date indicates that abundance and richness of small savanna mammals, in general (with important exceptions), is enhanced by vegetative cover (especially tall grass, but sometimes shrub cover) as refugia for these prey species amid a “landscape of fear,” particularly for diurnal, non-cursorial, and non-fossorial species. These species have been called “decreasers” in response to cover reduction, whereas a minority of small-mammal species have been shown to be “increasers” or disturbance-tolerant. Complex relationships between endogenous disturbances and small-mammal food resources are important secondary factors, but only six studies manipulated or measured food resources simultaneous to habitat manipulations. While more such studies are needed, designing effective ones for cryptic consumer communities of omnivorous dietary opportunists is a significant challenge.